THE INFLUENCE OF ZAKAT ON EDUCATION AND HEALTH AS A MEDIATING VARIABLE FOR POVERTY ALLEVIATION IN BANGKALAN SOCIETY - Zahro, Fatimatuz; Mashudi, Mashudi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study aims to analyze the effect of zakat on poverty alleviation in Bangkalan Regency by placing education and health as mediating variables. The approach used is quantitative with a case study method, using primary data from the results of questionnaires distributed to zakat beneficiary communities and regional zakat managers. The results of the statistical analysis show that zakat has a direct and significant effect on poverty reduction, and this effect increases significantly when mediated by education and health variables. These findings indicate that zakat not only functions as temporary assistance, but also as a tool for community empowerment if managed strategically. In addition, this study identifies that the effectiveness of zakat is highly dependent on zakat management policies at the regional level, including synergy between zakat institutions and local governments. This study provides theoretical contributions to the development of productive and practical zakat models to strengthen regional zakat policies that are oriented towards development. Recommendations are given for zakat to be made part of a regional development strategy that is integrated with the education and health sectors, in order to achieve sustainable poverty alleviation.